Rectus Abdominis Rhabdomyolysis: Report of 2 Cases. (15th May 2017) - Boyle, Jerome; Marks, Paul; Read, John
Abstract : Exercise‐induced rhabdomyolysis is an unusual clinical entity for physicians and one that is frequently misdiagnosed. With the ever‐increasing use of sonography by radiologists, sonographers, and sports physicians in the diagnosis of acute muscle injury, recognition of the typical sonographic appearance of rhabdomyolysis is paramount. Current literature using high‐resolution ultrasound equipment is limited, with much of the literature offering dated or incongruent descriptions. We describe the sonographic findings of hyperechoic muscle and a hypoechoic halo of edema in 2 proven cases of rectus abdominis rhabdomyolysis after exercise.